2019
DOI: 10.1155/2019/6372597
|View full text |Cite
|
Sign up to set email alerts
|

Public Transport Driver Identification System Using Histogram of Acceleration Data

Abstract: This paper introduces a driver identification system architecture for public transport which utilizes only acceleration sensor data. The system architecture consists of three main modules which are the data collection, data preprocessing, and driver identification module. Data were collected from real operation of campus shuttle buses. In the data preprocessing module, a filtering module is proposed to remove the inactive period of the public transport data. To extract the unique behavior of the driver, a hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
0
18
3
Order By: Relevance
“…Instead, we found that gyroscope and accelerometer data for 2 hours and 10 minutes per driver are sufficient to solve the same problem. Also, unlike [17] that suggested avoiding the z-axis, our results show that the highest performance achieved using data from all axes. xyz-Ac.…”
Section: A Sensitivity Analysis On Involved Axiscontrasting
confidence: 52%
See 1 more Smart Citation
“…Instead, we found that gyroscope and accelerometer data for 2 hours and 10 minutes per driver are sufficient to solve the same problem. Also, unlike [17] that suggested avoiding the z-axis, our results show that the highest performance achieved using data from all axes. xyz-Ac.…”
Section: A Sensitivity Analysis On Involved Axiscontrasting
confidence: 52%
“…• To train the GAN model, DWT of 6 signals of threedimensional accelerometer and gyroscope sensors data are fed to a specialized GAN to generate some augmented drivers' data. • In the feature extraction phase, we apply histograms of acceleration and gyroscope signals on overlapped win-dows, while [17] used only acceleration data. Although the GAN model works on DWT of driving data and yields promising results, the histogram feature overcomes DWT, spectral, temporal, and other statistical features for the driver identification phase.…”
mentioning
confidence: 99%
“…(ii) Driver factors. Virojboonkiate et al (2019) [44] proposed a driver identification system based on acceleration sensor data for PT systems. Mokarami et al (2019) [45] investigated 336 PT bus drivers in Tehran with two questionnaires and indicated that the organizational safety culture had positive effects on decreasing the unsafe behaviours of PT drivers and reducing PT accidents.…”
Section: Transportation Factormentioning
confidence: 99%
“…Based on Formulas (36) and (41), the individual value of the passenger for the energy factor during the time period t 1 ∼ t m can be calculated by Formula (44):…”
Section: Passenger Utility Analysesmentioning
confidence: 99%
“…After performing feature construction and feature selection, the sample features were input into a model integrating support vector machine (SVM), K‐nearest neighbours (KNNs), RF, and decision‐making trees (DT) with hyperparameter tuning, where the recognition accuracy rate was 88%. In [19, 20], a backward propagation (BP) neural network was used as the classifier, while the accelerator pedal and brake pressure signals or some improved features of vehicle acceleration were selected as the model input.…”
Section: Introductionmentioning
confidence: 99%